Biofloc technology system for improvement of the survival, growth, biochemical composition and physiology of African catfish (Clarias gariepinus burchell 1822) juveniles - Babatunde, Dauda Akeem (2018)
Biofloc technology system (BFT) is an in situ low-cost water quality management technique. It works on the principle of stimulating heterotrophic bacteria to convert the toxic nitrogenous waste into potentially consumable biomass. This has been successfully applied in shrimp and tilapia aquaculture. However there is little information on its application on other commercially important species including African catfish, Clarias gariepinus. This study aimed at establishing the most appropriate conditions for the nursery culture of C. gariepinus in a biofloc technology system. The study was conducted in four phases. The first phase investigated the effects of three different carbon sources with different characteristics, sucrose, glycerol and rice bran, on the biofloc formation, water quality, growth and survival performance and physiological status of the African catfish juveniles. There was no difference in growth or feeding efficiencies parameters but survival, liver glycogen content and overall water quality parameters were significantly higher in glycerol than other treatments. The use of rice bran led to mass mortalities, likely due to stress associated with elevated nitrogenous waste and less soluble rice bran acting as an irritant. Glycerol was further investigated in the second phase at different carbon/nitrogen (C/N) ratios, 0, 10, 15 or 20. The growth performance and overall health status of the African catfish were examined and subsequently, the fish in the different treatments were challenged with Aeromonas hydrophila to investigate their resistance to pathogenic bacteria. C/N ratio of 15 appears to be the best in the management of ammonia-N. Although chymotrypsin activities and physiological parameters were higher in all the BFT treatments than the control but growth performance was not different among the treatments. Meanwhile, C/N ratios of 15 or 20 led to a significantly higher resistance to disease compared to C/N ratio of 10 or the control. The third phase investigated the effects of feeding habit of cultured fish on the growth performance in BFT. The previously established glycerol and C/N ratio of 15 was used in BFT for a more efficient filter-feeding fish, lemon fin barb hybrid (LFBH) and African catfish, an inefficient filter feeder. The control system was a recirculating aquaculture system (RAS). Fish feeding habit affected the nutritional value of biofloc but not the biofloc formation. There was no difference in water quality between RAS and BFT except for nitrate-N which was higher in RAS. BFT led to substantially improved growth and feeding efficiencies performance in LFBH but the growth and feeding efficiencies in African catfish was only slightly higher in BFT than RAS. In the fourth phase, African catfish was cultured in BFT with differently processed rice bran as carbon sources. The rice bran was pretreated with a Bacillus sp. in either aerobic (cellular respiration; ResRB) or anaerobic condition (fermentation; FerRB) while raw rice bran (RRB) and RAS without carbon addition served as controls. The ammonia-N was significantly lower in RAS and FerRB in the first two weeks. However, the FerRB led to significantly improved growth and feeding efficiencies compared to the RAS or ResRB. The use of BFT with glycerol as the carbon source at C/N of 15 led to improved water quality management, and biochemical composition, physiological health status and diseases resistance of C. gariepinus in intensive nursery culture. In addition to efficient water quality management, FerRB led to improved growth and nutritional value of C. gariepinus juveniles in intensive nursery culture. The use of fermented rice bran is therefore recommended in BFT to culture African catfish. Meanwhile, there is need for further research on its optimum C/N ratio and the potentials to enhance the immunity and disease resistance of the fish culture in the system.